Effects of different fertilizers program to the yield potential of oil palm planted on peat soil area in Rompin, Pahang / Fazidah Rosli ...[et al.] - Rosli, Fazidah; Abdul, Shaiful Azlan; Lokman, Sufyan Thauri; Abdul Aziz, Noorshilawati (2014)
Peat soils have been regarded as problematic soils due to its natural state and are not suitable for the cultivation of most crops including oil palm. The research was done at three different oil palm plantations in Rompin, Pahang due to the reason where most of the oil palms planted on peat soil were located. The objectives of this study were to identify the types of fertilizer program on different peat soil area and to determine the most effective fertilizer program to the production of oil palm on peat soil area in Rompin Pahang. The research was done by collecting the secondary data from three different oil palm plantations on peat soil area in Rompin, Pahang. The oil palm plantations that involved in this study were Far East Delima Estate, Yayasan Pahang Sungai Kembar Estate, and Yayasan Pahang Sungai Mentelong Estate. Yield of the oil palm from these estates was taken to compare the effectiveness of the fertilizer program applied. The selection of oil palm field area was only restricted to oil palm planted on year 2006. The data obtained from these estates were analyzed using the statistical software called Statistical Packages for Social Science (SPSS). The result showed that there was significant difference between each fertilizer program to the yield of oil palm and Yayasan Pahang Sungai Mentelong Estate have the most effective fertilizer program. It is recommended that the best fertilizer program should also be introduced for the other low yield estate or smallholder as to increase their income.